Redefining Operational Excellence : New Strategies for Maximizing Performance and Profits across the Organization - Miller, Andrew, 1973- (AMACOM, 2014)
True operational excellence is not about ""lean"" or six sigma or any other methodology. Our world is too complex, too interconnected, and too fast moving for organizations to achieve dramatic results simply by eliminating waste and increasing standardization. Operational excellence is a mindset, and it requires a company culture that questions current models and focuses on adding value, making improvements, and increasing speed. Redefining Operational Excellence covers it all--processes, people, and operations--and shares specific strategies for finding money and performance boosts in areas b